HYDROTHERMAL TREATMENT CAMPURAN BIOMASSA DAN PREDIKSI NILAI KALOR HYDROCHAR - Cyrilla Oktaviananda; Ilma Fadlilah (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2019)
Energy needs in Indonesia always increase along with population growth and industrial growth. On the other hand, the abundant availability of biomass waste, especially teak sawdust and corn cobs, encouraged researchers to find the right technique for converting biomass waste to make the waste an alternative energy source. Hydrothermal Treatment is one of the techniques for thermal biomass conversion that can convert biomass into coal-like material called hydrochar. The biomass waste is in a heterogeneous or mixed state.The purpose of this study is to obtain the optimum composition of the biomass mixture to make solid fuels using the hydrothermal treatment method and to do a regression analysis to estimate heating value based on proximate analysis. The biomass waste used in this study was teak sawdust and corn cobs powder. The results from this study are the highest yield of hydrochar in the hydrothermal treatment process of teak sawdust which is equal to 68.1% and the highest calor value in the hydrothermal treatment of biomass with the same composition which is equal to 5402 cal / gram. An equation to predict the value calor hydrochar is HHV = 0.837 (% AC) +0.152 (% VM) +0.389 (% FC) -0.022 (% WC) with an absolute error of 4.11% and a relative error of 0.28 %.